Civilis ratio e Natura: Ipotesi di lettura di un argomento gaiano - D'Alessio, Raffaele (Tesserae iuris, 2024)
This essay deals with the exegesis of D. 4.5.8 in the light of Gaius’s description of the effects of the capitis deminutio on obligations. The author aims to reconstruct the context of excerpt where Gaius emphasizes the resistence of the obligationes quae naturalem praestationem habere intelleguntur to the capitis deminutio. In more specific terms, the author argues that Gaius had described the permanence of a number of debts of the filiifamiliarum emancipati or adrogati despite their status permutatio.